Peasantry and the Struggle for Land: The Case of Finca Térraba and Finca Chánguena (1985-2018) - Mora Calderón, José Antonio (2026)
This article derives from a Master’s Thesis in Geography and analyzes agrarian conflicts in Finca Térraba and Finca Chánguena (1985–2018) in Palmar Sur, Costa Rica, following the exit of the Banana Company in 1984. It examines the transition from banana enclave to cooperatives, contract farming, and ultimately peasant struggles for land. The study shows how evictions and land occupations reflect processes of multiterritoriality, power disputes, and peasant resistance, highlighting the 2015 blockade of the Río Grande de Térraba bridge as an expression of the ongoing rural struggle for land access and control by the peasantry.